PENGARUH KOMITMEN AFEKTIF DALAM MEMEDIASI KEPUASAN KERJA TERHADAP KINERJA KARYAWAN - Fara Fitriyani; Rio Radinal (Tirtayasa Ekonomika, 2016)
The purpose of this study was to determine the effect of job satisfaction on employee performance is mediated by affective commitment. The population in this study is a management accountant in a manufacturing company located in Tangerang district. The sampling method using purposive sampling with the number of samples that meet the criteria as much as 42 respondentsThe questionnaire was tested with reliability test and validity test. Hypothesis testing is done with the approach of Structural Equation Model (SEM) using software Partial Least Square (PLS) The results of this study indicate that a job satisfaction positive effect on Affective Commitment. Job satisfaction is also a positive effect on employee performance. And Affective Commitment  positive effect on employee performance Key word: job satisfaction, Affective Commitment, Employee Performance